Edukasi dan Pelatihan Pemanfaatan Kulit Kopi menjadi Teh Kaskara melalui Program PPK Ormawa di Desa Peron Kabupaten Kendal - Agnaf Naufal, Muhammad; Dias Nanda Revalina, Aurelia; Trismadya Primagati, Aira; Najwa, Rizqa; Nur Hidayat, Farid; Nabila, Hasna; Rahmawati, Rizki; Salwa, Laurellia; Julian Erdana, Rafael; Syafiul Anam, Muhammad; Haris, Amnan (Jurnal Dharma Indonesia, 2025)
The Ormawa Capacity Building Programme (PPK Ormawa) in Peron Village, Limbangan Subdistrict, Kendal Regency aims to improve the community's capacity in sustainable coffee management while optimising the use of coffee husks into cascara tea. Until now, coffee husks have tended to be discarded, potentially causing environmental pollution. The activities were carried out in three stages, namely preparation, implementation, and evaluation, involving the SEKAR Group as well as assistance from lecturers and students. The results of the programme showed a significant increase in the knowledge and skills of the participants. The Wilcoxon test showed a significant difference between the pre-test and post-test scores (p < 0.001). The attendance rate of participants reached 88%, with 76% of them able to independently practise cascara production. In addition to producing cascara as a new economic alternative, this programme also succeeded in changing the community's paradigm in viewing coffee waste as a valuable resource. The implementation of the zero waste and circular economy concepts through this activity supports sustainable local economic development and has the potential to be replicated in other coffee-producing villages.